Assessment of In vitro Anti-inflammatory Activity of Ginger and Diclofenac sodium combination (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The present research work aimed at evaluating the anti-inflammatory activity of Zingiber officinalis with Diclofenac sodium by HRBC membrane stabilization & Protein denaturation. The precluding of hypotonicity induced HRBC membrane lysis was taken as a measure of the anti-inflammatory activity. The percentage of membrane stabilization at different concentrations was performed for methanolic, hydro-methanolic ginger extract and diclofenac sodium. At a dose of 50µg/ml the maximum membrane stabilization 86.34% was found for Ginger extract(test) and at a dose of 500 mcg/ml membrane stabilization was found 91.16% for diclofenac sodium(standard) and the membrane stabilization for combination (ginger with diclofenac sodium) at a dose of 50µg/ml was recorded 86.43%, as the concentration increase(1000 mcg/ml) for combination(ginger with diclofenac sodium) the percentage protection was decreased. In vitro protein denaturation was performed by using egg albumin method. Maximum inhibition was observed in case of methanolic extract of ginger at concentration 1000mcg/ml and it was 78.83±5.17 and in hydro methanolic extract for Diclofenac sodium at concentration 1000mcg/ml and it was 63.37±2.78.Minimum inhibition observed in combination of methanolic extract of ginger and diclofenac sodium at concentration 1000mcg/ml and it was 25.27±1.76 and in combination of hydro-methanolic extract of ginger and Diclofenac sodium at concentration 1000mcg/ml and it was 28.23±3.14. The results of this study divulge that low dose combination of ginger and diclofenac sodium has higher anti-inflammatory activity than diclofenac sodium and ginger alone. With this initial study, research work could be extended further; therefore, the particular pharmacological action for the combination of ginger with diclofenac sodium could be discovered.